The Analysis of Customer Loyalty to Takeaway Restaurants in The Special Region of Yogyakarta - Laksana, Dwi Hari; Liestyana, Yuli; Pramesti, Aulia Rizqi Dyah Ayu (Jurnal Mebis, 2025)
The rapid advancement of technology and information has significantly impacted various sectors, including the food and beverage industry. As a fundamental human need, food plays a crucial role, and the increasing demand has led to substantial growth in this sector, particularly in restaurants and eateries. According to data from the Ministry of Industry (2023), the food and beverage industry grew by 5.35% in the first quarter of 2023, making it a major contributor to the non-oil and gas processing Gross Domestic Product (GDP). This study investigates the effects of service quality, product innovation, and customer satisfaction on customer loyalty at Takeaway Restaurants in the Special Region of Yogyakarta. Given the increasing competition in the food and beverage industry, understanding these factors is essential for maintaining a loyal customer base. Utilising a quantitative approach, data were collected from 123 repeat customers through online surveys administered via Google Forms. Using the SPSS analysis tool, IBM SPSS 23 Software version. The results indicate that all three variables significantly influence customer loyalty, with service quality having the most substantial impact. The findings highlight the importance of exceeding customer expectations through high-quality service and innovative product offerings. Additionally, recent challenges, such as concerns over hygiene practices, underscore the need for immediate improvements in service standards. Recommendations for Takeaway Restaurants include enhancing staff training, ensuring cleanliness, and fostering a positive dining experience to build long-term loyalty.